Assessment of an international breaststroke swimmer using a race readiness test - Thompson, K. G.; Garland, S. W. (International Journal of Sports Physiology and Performance, 2009)
Competitive swimmers routinely undertake a 7 x 200-m incremental step test to evaluate their fitness and readiness to compete. An exercise protocol more closely replicating competition swimming speeds may provide further insight into the swimmer`s physiological and technical readiness for competition. This case study reports data over a 3-year period from 11 Race Readiness Tests, which were completed, in addition to the 7 x 200-m test, as an attempt to provide the swimmer and coach with a fuller assessment. For this individual, data provided objective information from which to assess training status and race readiness following a transition from 200-m to 100-m race training. Data also raised a question as to whether a 100-m maximal effort 10 minutes before another one actually enhances performance owing to a priming effect.